Stoning for adultery in Christianity and Islam and its implementation in contemporary Muslim societies - Mohd Noor, Azman (IIUM Press, 2010)
This paper examines the scriptural bases of stoning for adultery in the two sister religions and its implementation in contemporary Muslim societies. Based upon archival and documentary research, this study found that stoning to death for adultery is prescribed in both the Bible and the Qur’ān. Christians, however, have abandoned this law and it is no longer practiced in any Christian-dominant country. With the expansion of Western imperialism, the same trend seems to be taking place in Muslim societies. There are a few Muslim countries that are trying to implement this law but they face a good deal of criticism from the Western media and other secular organizations, consequently, shying away from implementing this punishment in public.